2012
DOI: 10.1002/term.1629
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human skeletal stem and bone cell populations using dielectrophoresis

Abstract: Dielectrophoresis (DEP) is a non-invasive cell analysis method, which uses differences in the electrical properties of particles and the surrounding medium to determine cellular properties. Once determined, these properties can then be used as a basis for cell separation. The use of skeletal stem cells in the form of cell-based therapies is currently one of the most promising areas for disease treatment for a variety of skeletal and muscular disorders. However, the identification and sorting of these cells rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
2
29
0
Order By: Relevance
“…3.1 HL-60, MG-63, MSCs and skeletal stem cells MG-63, MSCs and SSCs are large cells with considerable heterogeneity. 47 The channel in the RT-DC device needed to be wide enough to allow the larger cells to flow through, but also not so large that smaller cells would not deform. 36 HL-60 are generally measured using 20 mm  20 mm cross-section channels, but for this work 30 mm  30 mm channels were used to accommodate the larger MG-63 and SSCs.…”
Section: Resultsmentioning
confidence: 99%
“…3.1 HL-60, MG-63, MSCs and skeletal stem cells MG-63, MSCs and SSCs are large cells with considerable heterogeneity. 47 The channel in the RT-DC device needed to be wide enough to allow the larger cells to flow through, but also not so large that smaller cells would not deform. 36 HL-60 are generally measured using 20 mm  20 mm cross-section channels, but for this work 30 mm  30 mm channels were used to accommodate the larger MG-63 and SSCs.…”
Section: Resultsmentioning
confidence: 99%
“…C mem is an important factor in understanding exocytosis, endocytosis and stimulus secretion mechanism that vary with biochemical cell cycle. Conductivity is a measure of the ability to conduct an electric field while the permittivity is a measure of cytoplasm or cell membrane to transmit the electric field [18]. …”
Section: Resultsmentioning
confidence: 99%
“…In cell biology, DEP can provide a quantitative measure of cellular properties and in our previous studies it was used to investigate cell separation and characterization along with identifying suitable buffers that could be used for cell studies [17]. DEP has been employed in a variety of cancer cell studies and is often used to characterizing cell sub populations [18]. We have also incorporated DEP as a tool to study and characterize dielectric properties of cancer cells at different stages of cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that CSCs are highly resistant to standard therapy 13 . Stemness-related markers in OS are ABCG2, Nestin, CD44, STRO-1, and Endoglin/CD105 [14][15][16][17] . Previously, we identified a novel protein doublecortin calmodulin-like kinase 1 (DCLK1) that is present in reserve quiescent stem cells in both the normal intestinal epithelium and in colon cancers 18,19 .…”
Section: Introductionmentioning
confidence: 99%